Tityus serrulatus: local and systemic repercussions after scorpion poisoning (Research, Society and Development, 2023)
The scorpion bite has great importance among accidents caused by venomous animals, both for the high incidence of cases, and for the possible severity of signs and symptoms that it can trigger. In Brazil, the scorpions of greater clinical relevance are found in the genus Tityus, especially the species Tityus serrulatus, due to the higher risk of morbidity and mortality, since it presents venom with greater toxicity. Thus, the present study aimed to analyze the main local and systemic repercussions after yellow scorpion poisoning described in the literature. This study is an integrative literature review, which used the platforms PubMed, Scientific Electronic Library On-line (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), and Google Scholar as a database for research of scientific articles, published between 2020 and 2023, in Portuguese and English. From the analyzed articles it can be observed that yellow scorpion poisoning triggers a series of clinical manifestations that can lead to a mild, moderate or severe condition depending on the stimuli that the toxin provokes in the body. Severe neurotoxic reactions consist especially of adrenergic effects that progress to acute pulmonary edema and heart failure. Therefore, it is of fundamental importance to provide medical care quickly, in which the administration of antivenom serum can be performed, if necessary.